USING INTERACTIVE TEACHING METHODS IN PRIMARY SCHOOL - Tursunova Zarina Ne’matovna (Prospects for innovative technologies in science and education, 2025)
The article is devoted to the issues of interactive teaching of primary school students and proposes interactive methods and technologies for use in primary school lessons, taking into account the psychological characteristics of primary school age.